2011
DOI: 10.1007/s00198-011-1584-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vertebral fractures in patients with rheumatoid arthritis: revisiting the role of glucocorticoids

Abstract: Rheumatoid arthritis is a risk factor of VF (OR = 6.5). VFA is a convenient tool for this diagnosis. Presence of VF is inversely related to the use of DMARD and glucocorticoids, enhancing the hypothesis that an appropriate control of the disease may be a protective factor against bone fragility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 36 publications
5
36
1
12
Order By: Relevance
“…Conversely, in the context of chronic inflammatory disease, it may be that controlling inflammation can lower the risk of inflammatory bone loss. A recent study reported observational data that, in patients with RA, the use of glucocorticoids was associated with an 83% lower chance of having vertebral fractures (28).…”
Section: Effect Of Steroids and Tnf Inhibitors On Bmdmentioning
confidence: 99%
“…Conversely, in the context of chronic inflammatory disease, it may be that controlling inflammation can lower the risk of inflammatory bone loss. A recent study reported observational data that, in patients with RA, the use of glucocorticoids was associated with an 83% lower chance of having vertebral fractures (28).…”
Section: Effect Of Steroids and Tnf Inhibitors On Bmdmentioning
confidence: 99%
“…We have shown that prevalence of non-vertebral fractures is a strong determinant of the risk of having vertebral fractures in patients with RA, 61 implying that the individual's skeleton is already of inadequate strength to withstand the trauma of daily living. Beyond GC use, these risk factors must be assessed in all patients, and all causes of secondary osteoporosis are added risk factors of fractures in patients with GCs.…”
Section: Role Of Patient Characteristicsmentioning
confidence: 96%
“…Например, в недавнем наблюдательном исследовании было показа-но, что при РА лечение ГК ассоциируется с 83% снижени-ем частоты переломов позвоночника [93]. По данным ме-таанализа S. Siu и соавт.…”
Section: безопасностьunclassified